2018
DOI: 10.1094/pdis-02-18-0339-re
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Pathogenicity of Botryosphaeriaceae Fungi Associated with Declining Urban Stands of Coast Redwood in California

Abstract: Coast redwood (Sequoia sempervirens) is among the most widely planted landscape trees in California (CA) but is in decline outside its natural range due to factors including prolonged drought and plant pathogens. We investigated associations of Botryosphaeriaceae fungi with declining coast redwood trees throughout CA. More than 100 samples were collected from 11 coastal and inland locations in CA. Fifty-nine Botryosphaeria-like fungal strains were isolated and 18 were selected for further study. Phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…However, in support of the true pathogen lifestyle, the inoculation tests with isolated D. corticola strains conducted on young, healthy, naturally established trees of black oak clearly demonstrated the pathogenicity of D. corticola. In a similar case in California, closely related Botryosphaeriaceae fungi Neofusicoccum australe, N. luteum, N. parvum, N. mediterraneum and Botryosphaeria dothidea have been isolated from declining coast redwood trees (Sequoia sempervirens) in the urban stands, which were severely drought stressed [9]. However, the inoculation tests with the isolates of these fungal species on potted healthy young trees of coast redwood clearly showed that Neofusicoccum species were true and very virulent pathogens, while B. dothidea was an opportunistic pathogen that did not cause severe infection on healthy trees [9].…”
Section: Diplodia Corticolamentioning
confidence: 85%
See 3 more Smart Citations
“…However, in support of the true pathogen lifestyle, the inoculation tests with isolated D. corticola strains conducted on young, healthy, naturally established trees of black oak clearly demonstrated the pathogenicity of D. corticola. In a similar case in California, closely related Botryosphaeriaceae fungi Neofusicoccum australe, N. luteum, N. parvum, N. mediterraneum and Botryosphaeria dothidea have been isolated from declining coast redwood trees (Sequoia sempervirens) in the urban stands, which were severely drought stressed [9]. However, the inoculation tests with the isolates of these fungal species on potted healthy young trees of coast redwood clearly showed that Neofusicoccum species were true and very virulent pathogens, while B. dothidea was an opportunistic pathogen that did not cause severe infection on healthy trees [9].…”
Section: Diplodia Corticolamentioning
confidence: 85%
“…In a similar case in California, closely related Botryosphaeriaceae fungi Neofusicoccum australe, N. luteum, N. parvum, N. mediterraneum and Botryosphaeria dothidea have been isolated from declining coast redwood trees (Sequoia sempervirens) in the urban stands, which were severely drought stressed [9]. However, the inoculation tests with the isolates of these fungal species on potted healthy young trees of coast redwood clearly showed that Neofusicoccum species were true and very virulent pathogens, while B. dothidea was an opportunistic pathogen that did not cause severe infection on healthy trees [9]. The other members of Botryosphaeriaceae family, such as B. dothidea [23,74,75] or Diplodia sapinea [76], are well-known opportunistic pathogens that dwell on the tree asymptomatically for months or even years, until the plant becomes weakened through any number of abiotic or biotic stresses (e.g.…”
Section: Diplodia Corticolamentioning
confidence: 85%
See 2 more Smart Citations
“…[7] pomegranate (Punica granatum) [8], peach (Prunus persica) [9] and walnut (Juglans regia) [10]. The forestry host plants include the coast redwood (Sequoia sempervirens) [11], Norfolk Island pine (Araucaria heterophylla) [12], Eucalyptus globulus [13,14], and Ginkgo biloba [15]. It is worth mentioning that most studies have focused basically on the isolation of the fungus from symptomatic or asymptomatic tissue, followed by molecular identi cation and pathogenicity testing through Koch's postulates; however, molecular information has been obtained only for the interaction between grapevine and N. parvum [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%